Diagnostic Testing for Degenerative Disc Disease - Michael W. Hasz (Advances in Orthopedics)
The diagnostic of degenerative disc disease should be reached with the help of various diagnostic studies. This article briefly review the information gained by the following tests: radiographs, computed tomography, magnetic resonance, and discography. The article explains how each modality provides a piece of the diagnostic puzzle and how discography confirms the origin of the patient’s pain.